JEMBATAN PADA GRAF FUZZY INTUITIONISTIC - Siti Alfiatur Rohmaniah; Bayu Surarso; Bambang Irawanto (Unisda Journal of Mathematics and Computer Science (UJMC), 2015)
An intuitionistic fuzzy graph consist of a couples of node sets V and set of edges E which the sum of degree membership and degree non membership each of nodes and each of edges in closed interval [0,1], the degree membership each of edges is less than or equal with the minimum of degree membership each of related nodes, and degree non membership each of edges is less than or equal with the maximum degree non membership each of related nodes. An intuitionistic fuzzy graph H can be said as intuitionistic fuzzy subgraph from intuitionistic fuzzy graph G if node set V of H is subset of node set V of G and edge set E of H is subset of edge set E of G. If there is an intuitionistic fuzzy graph G with nodes set of V and if each of edge has degree membership and non membership unconstantly, then G has at least one bridge. The theorem is proven to hold if the intuitionistic fuzzy graph has cycle.